SAT0257 IMAGING MANIFESTATIONS OF PULMONARY INVOLVEMENT IN TAKAYASU ARTERITIS. (13th June 2020) - Li, Z.; Ding, J.; Zheng, Z.; Zhu, P.
Abstract : Background: Takayasu arteritis (TA) is a form of chronic large vessel vasculitis. Recently, we found that some patients had lung manifestations and abnormal computed tomography (CT) results that cannot be explained by other causes. And so far, the prevalence of pulmonary features of TA is uncertain. Objectives: To investigate the imaging findings of lung involvement in patients with TA by high-resolution CT (HRCT) at a single center of China, and analyze the associations with mortality. Methods: A retrospective study was carried out of TA patients (n = 237, 200 women) who had routine HRCT scanning performed at the time of diagnosis from 2008 to 2018 at Xijing Hospital, Xi'an (China). Radiological manifestations of pulmonary involvement were evaluated from the HRCT images by two experienced radiologists. Patients with a confirmed diagnosis of pulmonary disorder (i.e., infections, tumors, except tuberculosis) have been excluded. Results: The median age of patients was 33 years (range 18-74), and the duration of disease was 66±55 months. Of all the patients, 57.8% (137/237) had abnormal lung HRCT results. Among them, 29.2% (40/137) of patients had pulmonary arterial involvement, including artery stenosis or occlusion. Mild pulmonary interstitial hyperplasia was the most common abnormal HRCT findings (27.4%, 65/237) observed in TA patients. Moreover, the frequencies of stripe/patchy shadows and nodule were 22.7% (53/237) and 15.6% (37/237), respectively. Pleural effusion was rare in these patients (10/237). Additionally, there are 9 cases of active pulmonary tuberculosis, 14 cases of suspected tuberculosis, and 9 cases of obsolete pulmonary tuberculosis. The common symptoms associated with lung were dyspnea (42%), cough (14%), chest pain (9.1%), and hemoptysis (4.9%). In a Cox regression model, there was no significant correlation between pulmonary involvement and mortality (P = 0.001). Conclusion: Pulmonary abnormalities on HRCT scanning is common among patients with TA. Apart from tuberculosis-related lesions and pulmonary arterial involvement, these manifestations are probably part of non-specific systemic inflammation of TA. Disclosure of Interests: None declared